Professional Training of the Future Primary School Teachers in the Czech Republic: Regulatory Bases (1989–2005) - BinytskaКateryna (Pedagogical Discourse, 2017)
The analysis of regulatory bases of professional training of the future primary school teachers in the Czech Republic has been made in the article. The relevance of this issue is also linked to the effective implementation of updated legal and regulatory basis of educational space of Ukraine according to European standards. The article reflects the scientific researches of domestic and foreign comparativists as for the professional preparation of the future teachers of primary school in the Czech Republic. It is mentioned that in the process of reforming the sphere of education, the Czech Republic used the experience of other European countries and recommendations of international organizations. The attention is focused on the fact that the first official document which determined the course of reforms was the Law «On Quality and Accountability in Education», prepared by the Ministry of education in 1994, which became the basis of the adopted in 2001, National programme of education development in the Czech Republic (so called White Book) that became the impetus for the future reforms in this area. It is noted that in the Czech Republic since 2001 in the national programme for the development of the education sector highly qualified teacher is considered as a major factor in the development of the education system. It is mentioned that the legal basis of the accession of the educational system of the Czech Republic to the Bologna process was enshrined in the new Law «On education» (2004). The conducted analysis of scientific literature proves that reforming the education system in the Czech Republic continued in the early twenty-first century and was particularly active during the integration of the country to the common European educational space. It is generalized that the legal documents reflect the intentions of the Czech government to reduce the differences in the existing programmes of teacher training, to bring them into conformity with the standards of the professional activity of teachers of the European countries, using them as the basis for building the system of pedagogical education. During this period other important documents that reinforce the new standards and requirements not only the changes in the system of professional teacher preparation in the Czech Republic have been adopted. Key words: regulatory basis, professional training, future teachers of primary school, Czech Republic.